6xsquared-3x+1forx=-2

Simple and best practice solution for 6xsquared-3x+1forx=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6xsquared-3x+1forx=-2 equation:


Simplifying
6xsquared + -3x + 1forx = -2

Reorder the terms:
6adeqrsux + 1forx + -3x = -2

Solving
6adeqrsux + 1forx + -3x = -2

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1forx' to each side of the equation.
6adeqrsux + 1forx + -1forx + -3x = -2 + -1forx

Combine like terms: 1forx + -1forx = 0
6adeqrsux + 0 + -3x = -2 + -1forx
6adeqrsux + -3x = -2 + -1forx

Add '3x' to each side of the equation.
6adeqrsux + -3x + 3x = -2 + -1forx + 3x

Combine like terms: -3x + 3x = 0
6adeqrsux + 0 = -2 + -1forx + 3x
6adeqrsux = -2 + -1forx + 3x

Divide each side by '6deqrsux'.
a = -0.3333333333d-1e-1q-1r-1s-1u-1x-1 + -0.1666666667d-1e-1foq-1s-1u-1 + 0.5d-1e-1q-1r-1s-1u-1

Simplifying
a = -0.3333333333d-1e-1q-1r-1s-1u-1x-1 + -0.1666666667d-1e-1foq-1s-1u-1 + 0.5d-1e-1q-1r-1s-1u-1

Reorder the terms:
a = -0.1666666667d-1e-1foq-1s-1u-1 + 0.5d-1e-1q-1r-1s-1u-1 + -0.3333333333d-1e-1q-1r-1s-1u-1x-1

See similar equations:

| 3z+5=1 | | x+(x-7)+3(x-7)=107 | | 10x-20=8x+16 | | 38-3x=-1-30x-42 | | 4x^2+11x-2=9x | | 2.5-11=28 | | 7x4y9/3 | | 2sin^2x=2sin+4 | | x=90+-1.5y | | 6x-x-8=2 | | Lny=-0.28 | | 7x=5y+30 | | 15=12+v | | -20-2n=24n+6 | | 2.5(6x+4)-5=12x+35 | | 3/x-7=21 | | y=17(x^2-9x+1) | | .089-7.18x=x | | 6b+34=8b | | 10+2x=16-4x | | 7x-2/6=1 | | (3x-18)+3x=180 | | -3[h+7]=-18 | | -4(7-1)= | | (a+4)(a+6)=63 | | 3x+13-4=5x+3 | | 25p^2-81= | | (z-7)(z+3)=-24 | | 2x^3+11x^2-67x-36=0 | | (5x+4)-(-8x)= | | 4x+y+2x+y= | | D=4n+na |

Equations solver categories